2018
DOI: 10.3390/galaxies6040118
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Explore Magnetized Cosmic Web with Forthcoming Large Surveys of Rotation Measure

Abstract: The warm-hot intergalactic medium (WHIM) is a candidate for the missing baryons in the Universe. If the WHIM is permeated with the intergalactic magnetic field (IGMF), the Faraday rotation measure (RM) of the WHIM is imprinted in linearly-polarized emission from extragalactic objects. In this article, we discuss strategies to explore the WHIM’s RM from forthcoming radio broadband and wide-field polarization sky surveys. There will be two observational breakthroughs in the coming decades; the RM grid and Farada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…We find a net value of ≈ 10 rad m −2 for the ∆RM 2 signal for random pairs, or an rms contribution of ≈ 7 rad m −2 for each component. This is consistent with the asymptotic value of 5-10 rad m −2 summarized by Akahori (2018) (figure 1 of Akahori) when clusters are excluded from the line of sight, and corresponds to magnetic fields ranging from 0.01 nG to 100 nG, going from voids into filamentary structures. When clusters are included, σ RM is predicted to be 4-8 times larger, which is not consistent with our data.…”
Section: The Igm Contributionsupporting
confidence: 87%
See 1 more Smart Citation
“…We find a net value of ≈ 10 rad m −2 for the ∆RM 2 signal for random pairs, or an rms contribution of ≈ 7 rad m −2 for each component. This is consistent with the asymptotic value of 5-10 rad m −2 summarized by Akahori (2018) (figure 1 of Akahori) when clusters are excluded from the line of sight, and corresponds to magnetic fields ranging from 0.01 nG to 100 nG, going from voids into filamentary structures. When clusters are included, σ RM is predicted to be 4-8 times larger, which is not consistent with our data.…”
Section: The Igm Contributionsupporting
confidence: 87%
“…These unknowns make it difficult to calculate an accurate and realistic limit. However, these effects are all embodied in cosmological MHD simulations, and so we compare our results to those, such as summarized recently by Akahori (2018). We find a net value of ≈ 10 rad m −2 for the ∆RM 2 signal for random pairs, or an rms contribution of ≈ 7 rad m −2 for each component.…”
Section: The Igm Contributionsupporting
confidence: 65%
“…Takuya Akahori studied the optimum frequency range to detect intergalactic magnetic fields with Faraday tomography. He concluded that for fairly small bandwidths around the optimum 500 − 600 MHz, intergalactic Faraday depths of ∼ 5 rad m −2 should become detectable [23,24].…”
Section: Intergalactic Magnetic Fieldsmentioning
confidence: 99%
“…The workshop had 64 participants. The biggest group of these were Japanese (24), there were 19 from Europe (6 Germany,4 Netherlands,4 Italy, 2 UK, 1 France, 1 Spain), 8 from North America (5 Canada, 3 US), 8 from Australia, and 4 from Asia other than Japan (2 South-Korea, 1 Russia, 1 India). A relatively large part of these were young researchers: 28 postdocs, 12 PhD students and 2 MSc students.…”
Section: Introductionmentioning
confidence: 99%